Shot-noise-induced lower temperature limit of the nonneutral plasma parallel temperature diagnostic - Adrianne Zhong; Joel Fajans; Jonathan S. Wurtele (EPJ Techniques and Instrumentation)
Abstract We develop a new algorithm to estimate the temperature of a nonneutral plasma in a Penning-Malmberg trap. The algorithm analyzes data obtained by slowly lowering a voltage that confines one end of the plasma and collecting escaping charges, and is a maximum likelihood estimator based on a physically-motivated model of the escape protocol presented in (Beck in Measurement of the magnetic and temperature dependence of the electron-electron anisotropic temperature relaxation rate. PhD thesis, 1990). Significantly, our algorithm may be used on single-count data, allowing for improved fits with low numbers of escaping electrons. This is important for low-temperature plasmas such as those used in antihydrogen trapping. We perform a Monte Carlo simulation of our algorithm, and assess its robustness to intrinsic shot noise and external noise. The assumptions in this paper allow for a lower bound for measurable plasma temperatures of approximately 3 K $3\,K$ for plasmas of length 1 cm $1\,cm$ , with approximately 100 particle counts needed for an accuracy of ± 10 % $± 10 %$ .